The extra climate benefits of solar farms - Lu, Zhengyao ; 0000-0002-5911-7110 (Nature Geoscience, 2025)
With solar projects worldwide expected to expand rapidly, understanding the ecosystem impacts is vital. Recent work highlights that optimizing land use strategies can significantly enhance carbon sequestration in the hosting ecosystem, making them a more effective tool in combating climate change.